(untitled) (Tanzania Journal for Population studies and Development, 2022)
This paper examines the type of communication systems used between indigenous and modern systems for climate change adaptation among rural communities like the Maasai of Ngerengere, Tanzania. The aim is to find out why such communities prefer particular communication systems. The study was informed by the conceptual framework of Western science versus indigenous knowledge binary tensions approach, and the interplay of indigenous and modern media systems for climate change adaptation. It employed the embedded case study design, with data being generated through interviews, documentary review and observation. The sample included the Maasai community, Ngerengere extension officers, and media experts and veteran journalists on climate change. The findings indicate that indigenous communication systems are the most preferred ones in communicating climate change adaptation information among the rural Maasai community of Ngerengere, followed by the use of both systems whereas modern communication systems play second fiddle to the indigenous ones. This article concludes that particular communication systems are preferred for climate change adaptation by rural communities because of their interactivity, proximity to meeting community needs, ability to effect change and their trustworthiness. It recommends that policy formulation and intervention should support indigenous communication systems by encouraging their usage in relevant rural areas, and the provision of supportive resources. Also, the governments and stakeholders should promote the use of indigenous-modern communication systems, such as community radios, which incorporate elements from both systems, for climate change adaptation, as well-received interventions among rural communities.